The Influence of Retention Statistics on a Short-Term Residential Substance Abuse Treatment Facility - Robertson, Ian (My University, 2005)
Residential addiction agencies are confronted by government with the expectation of collecting retention data. Retention as a statistic is being used to measure treatment effectiveness. The use of retention statistics to measure treatment effectiveness creates tension for managers and staff. This research will explore the use of retention statistics within the organization and the tension it creates for manager and frontline staff. The collection of retention data has shaped policies and practices that are "number-centered" versus "client-centered." Previous literature on retention statistics and personal interviews were methods utilized to gather data.
Influence of Retention Statistics on Substance Abuse Practice
Keywords: retention statistics; short-term resiedntial substance abuse treatment facility; residential substance abuse; substance abuse treatment facility